Adapting the principle of Sadd al-Zara'ah by the government in the regulation of product and service labelling - Osman, Suraiya; Jalil, Abdullaah; Ab Rahman, Suhaimi; Abu Bakar, Elistina; M. Safian, Yasmin Hanani (Muhammadiyah University Press, 2020)
The emergence of products and services using Islamic attributes as the tool of marketing is increasing nowadays. Various Islamic terms have been used on the label, packaging, and also as the trademark of the products and services, for example, Air Terapi Al-Quran, Mi Cap Masjid, Jus Sunnah, Bekam Sunnah, Valet Doa and in some instances the Quranic frame being hanged on the wall in non-Muslim restaurants and many more. Islamic attributes has been manipulated as a tool for marketing products and services. This trend has led to many bad effects on the consumer and the dignity of Islam itself. Islam is a religion and shall not be exploited for product marketing, and there are needs for a mechanism to control this matter. This paper will analyse the meaning of Islamic attributes that were used in marketing in Malaysia and their effect on the consumers and Islamic dignity. Next, this article will look into the Islamic principles that can be adopted by the government in controlling the use of Islamic attributes in marketing via the principle of Siyasah Shar’iyyah to uphold the Maqasid al-Shari’ah, particularly Hifz al-Din (Protection of Religion). This paper is conceptual in nature and is of library-based research using primary and secondary data. The government should take serious action in controlling this matter. The application of the concept of Sadd al-Zari’ah (Blocking the Means) is relevant to regulate this marketing strategy of the producers.